1996
DOI: 10.1111/j.1476-5381.1996.tb15592.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of verapamil on intimal thickening and vascular reactivity in the collared carotid artery of the rabbit

Abstract: 1. Intimal thickening is a common site for atherosclerosis. Therefore, we investigated whether the calcium entry blocker verapamil (10 mg kg-1 body weight day-1, s.c.) can retard intimal thickening and changes in vascular reactivity induced by a non-occlusive, silicone collar positioned around the left carotid artery of rabbits. The contralateral carotid artery was sham-operated and served as a control. 2. Verapamil and placebo (saline 0.1 ml kg-1, day-1, s.c.) treatments were initiated 7 days before placing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 50 publications
4
22
2
1
Order By: Relevance
“…The increased activities of MMP-2 and MMP-9 in the collared arteries suggest the possible involvement of these 2 gelatinases in the development of intima and/or vascular reactivity alterations of vascular tissue of rabbits in response to collaring. 22,33 Additionally, we observed that, in the placebo group, while the proMMP-2 band was found in both shamoperated and collared arteries, the active MMP-2 band was found only in collared arteries. This observation also suggests the possibility of involvement of MMPs in the collar-induced intimal thickening.…”
Section: Discussionmentioning
confidence: 85%
“…The increased activities of MMP-2 and MMP-9 in the collared arteries suggest the possible involvement of these 2 gelatinases in the development of intima and/or vascular reactivity alterations of vascular tissue of rabbits in response to collaring. 22,33 Additionally, we observed that, in the placebo group, while the proMMP-2 band was found in both shamoperated and collared arteries, the active MMP-2 band was found only in collared arteries. This observation also suggests the possibility of involvement of MMPs in the collar-induced intimal thickening.…”
Section: Discussionmentioning
confidence: 85%
“…22 In this study, con sis tent with pre vi o us re sults, col lar pla cing aro und the ca ro tid ar tery did not affect me an ar te ri al pres su re. 27,28 Be si des, ni fe di pine did not al ter res ting blo od pres su re in the pre sent study.…”
Section: -26mentioning
confidence: 84%
“…White rabbits (1.5–2 kg) of either sex were divided into 2 groups. The treatment protocol was as described previously (Ustunes et al , 1996). Briefly, the first group received a single administration of lacidipine (5 mg/kg/day, dissolved in 2.5 ml 0.5% aqueous solution of methylcellulose) via a gastric feeding tube.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the left carotid artery was surgically accessed and surrounded by a non-occlusive, flexible silicone collar (Ustunes et al , 1996, Yasa et al , 1999). The collar was 2 cm in length slightly touching the outer surface of the artery on each end.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation